Amenable mortality analysis in Mexico during the period 1998-2019 - García Hernández, Héctor (2022)
Background: The Mexican health system divides the population into people with and without social security. This organization generated health differences between both groups. Amenable mortality is an impact that if is studied between groups and territories it indirectly measures health inequities. Objective. Analyze the amenable mortality among Mexican population with and without social security from 1998 to 2019. Materials and methods. An ecological investigation was realized, obtaining standardized mortality rates of amenable mortality and two inequity measures for the population with and without social security, using an amenable mortality list adapted to Mexico. Results. At national level, the population with social security concentrates the greatest general, no amenable and amenable mortality. Looking at each category of amenable mortality we found that the mortality rates of Medical Services, Diabetes, Isquemic Hearth Diseases and Residual Causes were higher in social security population; while in Homicides, Acquired human Immunodeficiency Syndrome and Suicide and Intentional Injuries the opposite happens. At state level exist heterogeneity, but in 28 of 32 states the mortality rates were higher in social security population. It's the same in the ratio rates. The concentration index values reflect a little inequity between states. Conclusions. The population with social security had the greatest mortality. This doesn’t mean that an inequity exist in them, rather it reflect the influence of other variables (social determinants), and it's evidence with the concentration index.